Utilização de resíduos agronômicos da mandioca para fabricação de papéis especiais como recurso alternativo para a comunicação visual - Gonçalves, Solange Maria Leão [UNESP]; Benutti, Maria Antonia [UNESP] (My University, 2010)
The air part of the cassava is a residue which presents possibilities of being used as a non-wooden raw material in the production of pulp due to the fact that its 81 % of the adult plants air part, besides having high availability and presenting a high concentration of fibers. Studies were developed with the purpose of producing the pulps through the kraft process, which is a mix of the Na2S and NaOH in water heated up to the temperature of 160º C for about 90 minutes to the extraction of lignin. The paper sheets obtained in the practices went through an experimenting process. Studies related to the paper characteristics were accomplished in order to assess its use in the visual communication through printing techniques, silk screen, pictures and others graphical processes. The research results are able to conclude the utilization viability of this material in graphics communication.
Keywords: Agronomical residue; Maniva; Visual communication; Special paper